The Role of Subdistrict Election Committees in Increasing Electoral Participation Among Generation Zillennials - Kholikin, Rafi Akhsanul; Holivil, Ernestus (Jurnal Ilmu Administrasi Negara (JUAN), 2025)
The Zillennial generation faces multifaceted challenges in electoral participation, including political apathy, skepticism toward governance systems, and misinformation spread via social media. This study examines the role of the Subdistrict Election Committee (PPK) in Lakbok Subdistrict, Ciamis Regency, Indonesia, in addressing these barriers and enhancing voter engagement among Zillennials during the 2024 General Election. Employing a quantitative-descriptive approach, the research conducted interviews with 27 purposively sampled informants, including election officials, academics, party volunteers, and generational representatives. Data were analyzed using categorical identification based on ideal average value (Mi) and ideal standard deviation (SDi) to evaluate the effectiveness of PPK strategies. Findings reveal four critical roles of the PPK: (1) conducting technical guidance sessions from the General Election Commission (KPU) to district-level committees, emphasizing voter education and digital communication strategies; (2) improving accessibility and transparency through open data dissemination and inclusive outreach programs; (3) leveraging social media platforms like Instagram and TikTok to deliver engaging, visual electoral content tailored to Zillennial preferences; and (4) organizing offline voter education initiatives, such as workshops and community dialogues, to foster direct engagement. The study highlights that these roles significantly boosted Zillennial participation by addressing their unique needs for tech-savvy, transparent, and interactive communication. Notably, technical guidance sessions for PPK members (e.g., 25 sessions on voter education) correlated with increased youth turnout, while social media campaigns achieved high engagement rates through infographics and short videos. Recommendations include top-down optimization of PPK programs, structural integration of digital tools, and collaborative efforts with Zillennial communities to sustain democratic participation. This research contributes to electoral studies by demonstrating the importance of localized, adaptive strategies in bridging generational gaps in political engagement, particularly in Indonesia’s evolving democratic landscape.